Long noncoding RNA CHL1‐AS1 promotes cell proliferation and migration by sponging miR‐6076 to regulate CHL1 expression in endometrial cancer. Issue 3 (17th November 2019) - Shi, Yanmei; Zha, Jinfen; Zuo, Manzhen; Yan, Qian; Song, Huamei
Abstract: Endometrial cancer (EC) is deemed to be the most typical gynecologic malignant tumor. Despite the incidence of EC being lower in Asia than that in western countries, substantial increased incidence has been observed in the past few decades in Asia. Although various molecular testing methods and genomic science have developed, the overall prognosis is still disappointing. LncRNAs have been found to influence the progression of various cancers. CHL1‐AS1 has been found to be upregulated in ovarian endometriosis, nevertheless, the molecular mechanism and biological function of CHL1‐AS1 in EC have not been explored. In our exploration, both CHL1‐AS1 and CHL1 were upregulated in EC cells. Knockdown of CHL1‐AS1 or CHL1 inhibited cell proliferation and migration in EC. Furthermore, microRNA‐6076 (miR‐6076) could bind with CHL1‐AS1 or CHL1, and regulate the expression of CHL1. Finally, absence of miR‐6076 or overexpression of CHL1 can partially rescue the effect of CHL1‐AS1 knockdown or miR‐6076 upregulation on cell proliferation and migration, respectively. All in all, our research was the first endeavor to study the underlying mechanism of CHL1‐AS1 in EC and confirmed that CHL1‐AS1 regulated EC progression via targeting the miR‐6076/CHL1 axis, offering new insight into treating EC. Abstract : Both CHL1‐AS1 and CHL1 are upregulated in EC cells. Knockdown of CHL1‐AS1 or CHL1 inhibits cell proliferation and migration in EC. miR‐6076 could bind with CHL1‐AS1 or CHL1 and regulate the expression of CHL1